Partial discharge detection using Rogowski coils - Wong, Felicia Pei Shan (Nanyang Technological University, 2022)
The report investigates the effect of geometrical parameters on RC and its impact on sensitivity and frequency response. RC has been used to measure high impulse current measurement, but with tremendous improvement in the microprocessor, enabling to detect small pulse charge and have been used to obtain PD measurements. The project also proposed electromagnetic shielding to minimise noise-induced across the RC. The unshielded RC induced frequency noise at its output, reducing its SNR and its ability to detect low pulse charge. The shielded RC proved its effectiveness to suppress noise interference and higher SNR at a low pulse charge. It's vital to detect low pulse charge as it would indicate early degradation. The shielded RC and reference signal will be connected to oscilloscope to display and analyse through LabVIEW GUI.